دور معلمات رياض الأطفال في تنمية القيم الصحية للطفل لمواجهة التحدي الصحي العالمي لفيروس كورونا "كوفيد-19" - حنفي، محمد ماهر محمود; أبو حسين، ولاء محمد رضا حافظ Abu Hussein, Wala Mohammad Reda Hafez (جامعة سوهاج - كلية التربية, 2021)
هدف البحث إلى تسليط الضوء على التحدي الصحي العالمي (فيروس كورونا) الذي يواجه المجتمع المصري والعالم، وتحديد الدور الذي تقوم به معلمات رياض الأطفال في تنمية القيم الصحية للطفل لمواجهة فيروس كورونا (كوفيد ١٩). واستخدم الباحثان المنهج الوصفي، وأداة البحث المستخدمة هي الاستبانة، وتكونت من أربعة محاور و٤١ عبارة، وتكونت عينة الدراسة من (٢١٧) معلمة من معلمات رياض الأطفال في المدارس الحكومية والخاصة. ومن النتائج التي توصل إليها البحث أن لمعلمات رياض الأطفال دورا إيجابيا وفعالا ومهما في تنمية ثقافة القيم الصحية للطفل لمواجهة التحدي الصحي العالمي فيروس كورونا (كوفيد -١٩)، والتي تتعلق بالنظافة الشخصية، والنظافة العامة، وتناول الطعام، والوقاية من الأمراض المعدية، كما أن لمعلمات رياض الأطفال دورا بارزا في تطبيق الإجراءات الوقائية داخل الروضة لمواجهة التحدي الصحي العالمي فيروس كورونا (كوفيد – 19).
The purpose of this research is to shed light on the global health challenge (Coronavirus) facing the Egyptian community and the world, and determine the role that kindergarten teachers play in developing the child's health values to face Coronavirus (Covid 19). The researchers used the descriptive method. The research used a questionnaire and it consisted of four axes and 41 statements. The study sample consisted of (217) kindergarten teachers in public and private schools. The results of the research show that kindergarten teachers play a positive, effective and important role in developing a culture of healthy values for children to face the global health challenge Coronavirus (Covid-19), which relates to personal hygiene, general hygiene, food intake and the prevention of infectious diseases also kindergarten teachers play an obvious role in applying preventive measures inside the kindergarten to face the global health challenge Coronavirus (Covid-19).
Keywords: التعليم قبل المدرسي -- معلمات رياض الأطفال -- التوعية الصحية -- فيروس كورونا